Production of graphene layer by liquid-phase exfoliation with low sonication power and sonication time from synthesized expanded graphite - Guler, Omer; Guler, S. Hale; Selen, Veyis; Albayrak, Muhammet Gokhan; Evin, Ertan (Taylor & Francis Inc, 2016)
Multi-layer graphene was produced through synthesized expanded graphite (EG) liquid exfoliation using organic solvent. Hexagonal graphite (HG) was used as a starting material. HG was mixed with an acidic mixture, dried, rand subjected to thermal treatment. After this process, EG was obtained. This obtained EG was sonicated for 1h via an ultrasonic homogenizer by blending an organic solvent. Samples were subjected to SEM, TEM, FTIR, and UV-Vis/NIR spectroscopy investigations. After the investigations, it was shown that nano-size graphene sheets were obtained.
Keywords: Graphene; liquid-phase exfoliation; expanded graphite